Unidades de ensino potencialmente significativas para a aprendizagem na matemática: um olhar de professores do Rio Grande do Sul a partir de uma oficina pedagógica - Barros, Jucelaine Lages de (2022)
The main objective of the present research is to investigate how the construction of Potentially Significant Teaching Units (PSTU) for teaching mathematics content is developed with teachers of different grade levels, from a Pedagogical Workshop on Critical Significant Learning Theory (CSLT). The studies were developed over two school semesters, with a partnership between two educational institutions, the Universidade Federal do Pampa (UNIPAMPA) and the Universidade Federal de Santa Maria (UFSM). In the first semester of 2020, it was worked on Active Methodologies, this step was in charge of teachers from Unipampa - Itaqui Campus, and then, in the second semester, it was continued with the Pedagogical Workshops on the Theory of Significant Learning (TSL), CSLT, PSTU and Concept Maps, which were in charge of the author and the supervisor of this research, both from UFSM, emphasizing the area of Mathematics Education. The workshops were conducted remotely, due to the COVID-19 pandemic, since they needed to undergo modifications during their organization and application process, throughout the year 2020. The study in question had as its main focus the Pedagogical Workshops, which are based on Marco Antônio Moreira's Critical Significant Learning Theory, and also has a qualitative, descriptive, and interpretive character, since the methodological procedure adopted was the Case Study. For data collection, questionnaires, word clouds, concept maps, and evaluations using PSTU were used, the latter being used as a learning resource and also as a means of evaluation. The development of the research foresees six stages: Stage 1: Bibliographical revision of Dissertations and Theses about PSTU, in the period of the last 5 years, that involve PSTU and teacher education in Mathematics; Stage 2: Application of a diagnostic test, in order to verify the initial conceptions of the teachers about preferences for mathematical contents and about the attribution of meanings and criticality to the contents worked on, and to know better the target public of the research, in relation to their formation and professional experience; Stage 3: Elaboration and Development of the pedagogical training workshop on TSL and CSLT, lasting 70 hours; Stage 4: Development of a PSTU for the teaching of mathematical contents worked by the teachers participating in the workshop; Stage 5: Analysis of the PSU construction process by the teachers participating in the workshops; and, Stage 6: Evaluation of the whole process during the workshops, considering the sequential aspects of CSLT. From the data collected, a descriptive and interpretive analysis of the process of the construction of the PSTU was made, taking into account the process coding schemes, according to Bogdan and Biklen, used to put the data under study in an organizational way.